Age and sex differences in burnout, career satisfaction, and well-being in US neurologists. (13th November 2018) - LaFaver, Kathrin; Miyasaki, Janis M.; Keran, Christopher M.; Rheaume, Carol; Gulya, Lisa; Levin, Kerry H.; Jones, Elaine C.; Schwarz, Heidi B.; Molano, Jennifer R.; Hessler, Amy; Singhal, Divya; Shanafelt, Tait D.; et al.
Abstract : Objective: To examine age and sex differences in burnout, career satisfaction, and well-being in US neurologists. Methods: Quantitative and qualitative analyses of men's (n = 1, 091) and women's (n = 580) responses to a 2016 survey of US neurologists. Results: Emotional exhaustion in neurologists initially increased with age, then started to decrease as neurologists got older. Depersonalization decreased as neurologists got older. Fatigue and overall quality of life in neurologists initially worsened with age, then started to improve as neurologists got older. More women (64.6%) than men (57.8%) met burnout criteria on univariate analysis. Women respondents were younger and more likely to work in academic and employed positions. Sex was not an independent predictive factor of burnout, fatigue, or overall quality of life after controlling for age. In both men and women, greater autonomy, meaning in work, reasonable amount of clerical tasks, and having effective support staff were associated with lower burnout risk. More hours worked, more nights on call, higher outpatient volume, and higher percent of time in clinical practice were associated with higher burnout risk. For women, greater number of weekends doing hospital rounds was associated with higher burnout risk. Women neurologists made proportionately more negative comments than men regarding workload, work–life balance, leadership and deterioration of professionalism, and demands of productivity eroding the academic mission. Conclusions: We identified differences in burnout, career satisfaction, and well-being in neurologists by age and sex. This may aid in developing strategies to prevent and mitigate burnout and promote professional fulfillment for different demographic subgroups of neurologists.